Impacts of the COVID-19 pandemic on the mental health of the elderly at an Basic Health Unit (UBS) in Guanambi, Bahia, Brazil (Research, Society and Development, 2023)
Objective: to determine the impacts of the COVID-19 pandemic on the mental health of the elderly in a Basic Health Unit (UBS) in Guanambi (BA). Method: This is a quantitative cross-sectional study, carried out in the second half of 2022, in which data associated with the COVID-19 pandemic were analyzed through a self-administered questionnaire and the presence of depressive and anxiety-phobic symptoms were investigated through the Geriatric Depression Scale (GDS) and the Geriatric Anxiety Inventory (GAI). Data were analyzed using descriptive statistics and bivariate analysis using ANOVA and Student's T test. Results: The sample contained 42 elderly people, most of them did not have COVID-19 (78.6%), however 66.7% had family members diagnosed and 61.9% lost someone to the disease. Overall, they scored low on the GDS and GAI, averaging 3.54 ± 2.49 on the GDS scale and 6.57 ± 5.82 on the GAI scale. The strongest association was given between the loss of someone known to COVID-19 and a higher score on the GAI scale (p value 0,003). There wasn’t relationship between GAI and GDS scores and gender, education level, monthly family income, need for medical care and economic losses during the pandemic, and the presence of comorbidities at the time of COVID-19 diagnosis. Conclusion: the loss of acquaintances due to COVID-19 may be associated with the development of depressive symptoms and, mainly, anxiety. Economic losses resulting from the quarantine did not seem to influence the prevalence of psychiatric symptoms.